2017
DOI: 10.1007/s12192-016-0757-6
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of small heat shock proteins with light component of neurofilaments (NFL)

Abstract: The interaction of human small heat shock protein HspB1, its point mutants associated with distal hereditary motor neuropathy, and three other small heat shock proteins (HspB5, HspB6, HspB8) with the light component of neurofilaments (NFL) was analyzed by differential centrifugation, analytical ultracentrifugation, and fluorescent spectroscopy. The wild-type HspB1 decreased the quantity of NFL in pellets obtained after low-and high-speed centrifugation and increased the quantity of NFL remaining in the superna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…These changes may depend on the aggregation of NF proteins with mutant HSPB1 [333,351,356] or their reduced axonal transport, which correlates with increased NF phosphorylation by Cdk5 [357]. Furthermore, in vitro studies of Nefedova et al hinted for several HSPB1 mutants an increased interaction with NFs, although the differences did not reach statistical significance [331]. A direct role for NFs in the pathogenesis was indicated by Zhai and colleagues, who showed that neurotoxicity of HSPB1 p.S135F for cultured motoneurons was diminished in NFL-deficient cells [356].…”
Section: Downstream Pathomechanismsmentioning
confidence: 98%
See 1 more Smart Citation
“…These changes may depend on the aggregation of NF proteins with mutant HSPB1 [333,351,356] or their reduced axonal transport, which correlates with increased NF phosphorylation by Cdk5 [357]. Furthermore, in vitro studies of Nefedova et al hinted for several HSPB1 mutants an increased interaction with NFs, although the differences did not reach statistical significance [331]. A direct role for NFs in the pathogenesis was indicated by Zhai and colleagues, who showed that neurotoxicity of HSPB1 p.S135F for cultured motoneurons was diminished in NFL-deficient cells [356].…”
Section: Downstream Pathomechanismsmentioning
confidence: 98%
“…Protection of the cytoskeleton from stress-induced damage and modulating cytoskeletal structure and function are considered to be among the principal functions of HSPB1. Similarly to CRYAB, HSPB1 shows stress-induced cytoskeletal and myofibrillar association [197,203,323], and it has been shown to protect and modulate all major cytoskeletal systems: actin [184,[323][324][325][326][327][328][329], intermediate filaments [208,210,330,331], microtubules [332], and titin [204]. In this regard, of particular relevance for muscle could be the recently characterized mechanosensitive functions: HSPB1, which is phosphorylated in response to mechanical stress, was shown to promote actin remodeling in strained regions of the actin cytoskeleton [329] and to modulate reversible unfolding upon filamin caused by mechanical stress [184].…”
Section: Hspb1mentioning
confidence: 99%
“…sHSP functions are very diverse and include chaperone-like activity and modulation of cytoskeleton stability (Aquilina et al 2004;Arrigo 2013;Bryantsev et al 2002;den Engelsman et al 2005;Ecroyd et al 2007;Gaestel 2002;Lambert et al 1999;Lavoie et al 1995;Mehlen et al 1997;Morrison et al 2003;Morrow et al 2015;Rogalla et al 1999;Rouse et al 1994;Theriault et al 2004;Webster 2003). As a consequence of their role as chaperones towards diverse clients, which influences client fate (refolding or degradation) and due to their role as stabilizing agents of the cytoskeleton, sHSPs participate indirectly in the regulation of complex processes such as the response and adaptation to cell stress, thermotolerance, cell differentiation, cell movement, cell apoptosis, and development (Arrigo 2000;Arrigo and Ducasse 2002;Arrigo and Gibert 2014;Balogi et al 2008;Benjamin et al 1997;Bruey et al 2000;Doshi et al 2009;Haslbeck et al 2016;Hong and Vierling 2000;Kamradt et al 2002Kamradt et al , 2005Lavoie et al 1993;Lavoie et al 1995;Litt et al 1998;Nicholl and Quinlan 1994;Parcellier et al 2006;Park et al 2016;Perng et al 1999a, b;Qian et al 2009;Quinlan and Van Den Ijssel 1999;Takayama et al 2003;Tanguay and Hightower 2015;Webster 2003). Thus, malfunction of sHSPs can have adverse effects in a number of diseases and is the cause of a wide range of p...…”
Section: Introductionmentioning
confidence: 99%
“…Test tube studies are also required to test and compare the chaperone-like activity of the various sHSPs toward a specific subset of substrates, highlighting how structural differences in sHSPs result in different chaperone power. Johannes Buchner (Germany) reported the first comparative analysis of eight human sHSPs to determine their chaperone properties (Mymrikov et al 2016). Aggregation assays using several model substrate proteins under standard conditions revealed differences between assays and sHSPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation